Theoretical assessment of different ultrasonic configurations for delamination defects detection in composite components - Kappatos, V.; Asfis, G.; Salonitis, Konstantinos; Tzitzilonis, V.; Avdelidis, Nicolas Peter; Cheilakou, E.; Theodorakeas, P. (Elsevier, 2017)
It is well known that structures’ safety is crucial and of great importance. Part of their maintenance procedure is structural inspection, which is currently performed with the aid of Non Destructive Testing techniques, aiming to detect structural defects in damaged or flawed components and prevent a catastrophic failure by substituting or repairing them. The objective of this work is the theoretical assessment of different ultrasonic configurations that could maximize delamination defect detection in composite components. Modeling study was performed using simulation software, where physical models representative of laminated Carbon Fiber Reinforced Polymer composites, consisting of a variety of artificial delamination defect modes (different sizes and depth), were numerically tested. Different ultrasonic configurations on both the positioning and the firing of the probe's elements including Phased Array delay timings and sampled array techniques were investigated and are presented in this paper. The potential of Full Matrix Capture data acquisition technique, modelled here, along with the post processing Total Focusing Method reconstruction approach is also assessed in terms of their ability to enhance defect detectability and visualization.
Keywords: Ultrasonic; Assessment; Sensor Configuration; Phased Array; Composite